STUDI KRITIS PERDA RENCANA TATA RUANG WILAYAH (RTRW) DI KABUPATEN MAMUJU TENGAH (TELAAH SIYASAH SYAR’IAH) - Ahmadi, Muh; Umar, Subehan Khalik (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2020)
This thesis discusses a critical study of Regional Regulation on Regional Spatial Planning related to the arrangement of estate control in the Mamuju Regency amid the study of Siyasah Syar’iyyah, namely: 1. What is the concept of regional regulation on Regional Spatial Planning in Central Mamuju Regency? 2. How is the implementation of the Regional Regulation on Regional Spatial Planning Regarding Plantation Area Arrangement? 3. What about Siyasah Shar’iyyah Logging on Regional Spatial Planning Regulations in Central Mamuju Regency? This type of research is classified as qualitative. There are two research data sources, primary data and secondary data. which consists of local government related to the plantation area. Furthermore, the data collection methods used are documentation, observation, and interviews, then the techniques in processing data, have several stages, namely: Clarification of data (picking data), data reduction (reducing data), editing (editing data that is wrong). Based on the research results of the Regional Regulation on Regional Spatial Layout Plan in Central Mamuju Regency on Plantation Spatial Planning, it cannot be implemented rigidly. This is possible a). A very rapid population increase that affects the supply of various needs. b). Progress and growth of the national economy and global economy which caused a lot of foreign direct investment to enter various regions of Indonesia, c). The need for physical facilities and infrastructure, both those needed by the government and the private sector, as well as the community members themselves, is something that must be understood carefully, proportionally, and in harmony with spatial planning.